The Sacred and the Sinister: A Musicological Inquiry into Ave Satani in The Omen - Indrawan, Andre; Julio, Christofer; Van Ness, Edward Christian (Resital: Jurnal Seni Pertunjukan, 2024)
No horror film song has won the Academy Award for Best Original Song, yet Jerry Goldsmith’s Ave Satani from The Omen (1976) remains the only nominee. Its fusion of Latin liturgical elements, ritualistic rhythms, and dissonant harmonies enhances the film’s dark symbolism. This study analyzes Ave Satani through a musicological approach, exploring its composition, thematic role, and cultural impact. Findings reveal its significance in reinforcing The Omen’s conflict between good and evil, highlighting the importance of interdisciplinary perspectives in film music analysis and the potential of thematic scoring to deepen cinematic storytelling.